Homoclinic Solutions in Bazykin’s Predator-Prey Model - Al-Hdaibat, Bashir (Discontinuity, Nonlinearity, and Complexity, 2026)
In this paper we derive an explicit second-order approximation of the homoclinic solutions in the Bazykin’s predator-prey model. The analytic solutions are compared with those obtained by numerical continuation.